(untitled) (Research, Society and Development, 2021)
To analyze the labeling adequacy of Greek Yogurts with the current Brazilian legislation for packaged products, which includes the list of ingredients, the content of proteins, carbohydrates and sugars, the amount of saturated fat and the presence of additives. This research was done in products of this kind available in João Pessoa - Paraíba supermarkets. The data collected was about the list of ingredients, nutritional facts and the information contained on the labels. The collected data were tabulated on the Excel ® spreadsheet and analyzed statistically by Principal Component Analysis (PCA). 107 yogurts from 10 different brands were evaluated, in which all yogurts were in compliance with current legislation. As of nutritional composition, the products had high amounts of added sugars, saturated fat and additives, which differs from the original composition of the original Greek yogurt recipe; however, the G brand had the lowest content of added substances and the best nutritional quality. The results show that consumers need to pay attention to product labels to make better choices, nutrition professionals are expected to better understand the composition of these yogurts to effectively guide their consumption.